THE ROLE OF MARKETING AMBIDEXTERITY TO UPSCALING SME’S BUSINESS PERFORMANCE - Ramadani, Alya Nisa; Riptiono, Sulis; Wibawanto, Sigit (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2025)
This study aims to examine entrepreneurship orientation, online marketing capability, and marketing ambidexterity on fashion business performance in SMEs in Central Java. A total of 230 fashion business owners selected using a simple random sampling technique were involved in this study. Data were analyzed using SEM-Amos. The study's results indicated that marketing ambidexterity represented by market-driving orientation was significant to fashion business performance. In contrast, market-driven orientation was not proven to influence business performance. In addition, marketing ambidexterity was influenced by online marketing capability. Furthermore, the other factors that could improve SME fashion business performance are entrepreneurship orientation and online marketing capability. Although entrepreneurship orientation was significant toward business performance, it did not influence online marketing capability. The implication of this study is that SME businesses should take a business approach that focuses on understanding and fulfilling customer needs and desires by optimizing online marketing capabilities and paying attention to entrepreneurship orientation.